Beyond borders: How geopolitics is reshaping trade - Costanza Bosone; Giovanni Stamato (European Central Bank (ECB), 2024)
Rising trade tensions, a spate of trade-inhibiting policy measures and a weakening of multilateral institutions have sparked a growing concern about the potential implications of global trade fragmentation. Yet, empirical evidence that geopolitical considerations are already materially affecting trade flows is scant. In this study, we quantify the impact of geopolitical tensions on trade of manufacturing goods over the period 2012-2022 in a structural gravity framework. To capture the influence of geopolitical tensions, we use a measure of geopolitical distance based on the UN General Assembly voting. The econometric analysis offers robust evidence that geopolitical distance has become a trade friction and its impact has steadily increased over time. Our results suggest that a 10% increase in geopolitical distance, like the observed increase in the US-China distance since 2018, is associated with a reduction in trade by about 2%. Our findings also highlight a differential and stronger impact on advanced economies and the emergence of friend-shoring.
Keywords: F10; F13; F14; F15; 330; rade fragmentation; structural gravity models; geopolitics; friend-shoring; trade costs